Pulmonary mucormycosis associated with medical marijuana use - Stone, Taylor; Henkle, Joseph; Prakash, Vidhya (Respiratory medicine case reports, 2019)
A 66-year-old man with diabetes presented to the hospital with a two-month history of dyspnea, cough, rust-colored sputum, night sweats and 20 pound weight loss. He had begun smoking medical marijuana 3 months earlier. CT of the chest showed multiple bilateral large ground glass opacities with surrounding consolidation. Infectious workup was negative. BAL was non-diagnostic. He was treated with broad spectrum antibiotics without improvement. VATS was performed and cultured lung tissue grew Rhizopus species. He was started on intravenous liposomal amphotericin B and micafungin and then transitioned to oral posaconazole after two weeks. Repeat CT two months later showed stable size of the cavities. One month later he died of massive pulmonary hemorrhage. Here we document what we believe is the first known case of pulmonary mucormycosis associated with medical marijuana use.